THE EFFECT OF F/M RATIO TO THE ANAEROBIC DECOMPOSITION OF BIOGAS PRODUCTION FROM FISH OFFAL WASTE - Agus Hadiyarto; Budiyono Budiyono; Seno Djohari; Indra Hutama; Wahid Hasyim (Waste Technology, 2015)
Biogas is a gas produced from the anaerobic decomposition of organic compounds. In the production of biogas from anaerobic digestion, value of F/M ratio shows a ratio between the mass of food available in the waste substrate with a mass of microorganisms that act as decomposers. F/M ratio is too small causing microbes could not metabolize perfectly and vice versa on the value of the ratio F / M overload resulting metabolic imbalance. The purpose of this study was to assess the effect of F/M ratio to optimal production of biogas from fish offal waste. The process of anaerobic digestion is conducted in the biodigester with four-liter volume and batch system operated at ambient temperature for 38 days. As a raw material, fish offal and microbial sludge obtained from the curing of fish and river mud discharges in the region of Bandarharjo, Semarang, Central Java. F/M ratio is set at 0.2, 0.4, and 0.6 are derived from sewage sludge VSS weight ratio of fish offal with sludge containing microbes. The addition of micronutrients supplied with a concentration of 0.4 mg/liter. Yield maximum methane gas obtained was 164,7 l/kg CODMn when the ratio F/M was 0.2. Based on the results of the study, found that the ratio F/M affect the amount of biogas produced. Meanwhile, the retention time (HRT) is only influenced by the ratio F/M.